Pohjoinen voimaannuttavana paikkana: Nuorten tila- ja paikkakokemukset Anna-Liisa Haakanan teoksissa Ykä yksinäinen ja Kehnompi Kettunen - Kanto, Kati (AVAIN - Kirjallisuudentutkimuksen aikakauslehti, 2017)
The North as an Empowering Place:Young People’s Experiences of Space and Place in the Novels Ykä yksinäinen (”Lonely Ykä”, 1980) and Kehnompi Kettunen (“The Inferior Kettunen”, 1986) by Anna-Liisa Haakana The subject of my article is Anna-Liisa Haakana’s two novels for young people: Lonely Ykä (My One-Legged Friend and Me) (1980) and The Inferior Kettunen (1986). By analyzing Haakana’s novels I study how young people living in northern Finland experience different spaces and places. The main characters of the novels, 15-year-old Ykä and Jukkis, discover their own sexuality, relationships and themselves in the space of nature. It leads them to feel deep love and attachment, topophilia, toward the North. Important places are also the isolated cabins in the middle of nature, where the boys can spend nights and train to cook and manage themselves. The nature functions as a compensation for the lack of such places that are usually important to young people. The boys meet friends in the center of the village as well, usually in cafés of gas or bus stations. These kind of places can increase their feelings of anxiety and hate, topophobia of the North: competition among young people, drinking and other troubles are born there. Other reasons for topophobia are the state of unemployment, the tattle of others, who know one another well, and the negative TV news from countries stricken by war and famine. Despite the topophobia present in these books, the North is depicted as a place where the young characters of Haakana’s books feel such a deep love, topophilia, toward the North, that they want to stay there. Their feelings of topophobia are only temporary.